PERILAKU AGRESIVITAS PAJAK KORPORASI DI INDONESIA DALAM PERSPEKTIF KINERJA KEUANGAN DAN TATA KELOLA PERUSAHAAN - Latifah, Hanum Bani (Jurnal Akuntansi AKUNESA, 2020)
Tax aggressiveness is actionttaken to minimize the burden of the taxpayerrreceives tax payable. The moreeefficient the tax burden of state revenues frommtaxes will also decrease. This study aims to explained the effect of Leverage, Institusional Ownership, Independent Commisioners and Audit Commitee on Tax Aggressiveness. The sample used is sector manufacturing companies listedoon the BEI in the 2013 until 2017. The sample selection using purposive sampling method.The sample in this study as many 201 sample. Multiple linear regression analysis with SPSS 23 program was used to analyze the data of this study. The results showed that Leverage has positive effect on tax agressivness, because the greater the level debt, so the greater of the company takes tax aggressivesness. Institusional Ownership has negative effect on tax aggressiveness. Independent Commisioners has negative effect on tax aggressiveness. Audit Commitee has a negative effect on tax aggressiveness.